Development of Cyber Literature on Human Values and Nationalism in The Poetry of Ibrahim Tuqan: Semiotic Structural Analysis - Jubaidah, Siti; Ilham, Andri; Bahtiar, Ihwan Rahman (Kalimatuna: Journal of Arabic Research, 2023)
This research aims to obtain a clear description of the kinds of human values and nationalism contained in Ibrahim Tuqan's poetry. This research uses a descriptive method through content analysis. This research is focused on the values of humanity and nationalism contained in Ibrahim Tuqan's poetry. The research instrument was the researchers themselves assisted by three classification tables. The first table contains the analysis column of Charles Sanders Pierce's semiotic study which consists of icons, indexes, and symbols. Then the second table contains an analysis of human values in Ibrahim Tuqan's poetry. Then the third table contains an analysis of the values of nationalism in Ibrahim Tuqan's poetry.